(3GdeSJTGQ aj EOGQI GdTQGA h GdJLGQI GdOhdjI (B:s (3YbhO GdTQGA , GdJaGhV eY GdehQOjf , GdTMf , GdYWGAGJ , GdYbhO GdGdcJQhfjI (B/s - (3GdWQGhfI, YeQ WdYJs ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2012)
(3CgOGa GOGQI GdeTJQjGJ h GdYWGAGJ h GddhGRe , WQb GdTQGA h GLQGAGJ JfajP GdYWGAGJ , TQhW CeQ GdTQGA h GdTQhW GdYGe ddONhd aj GdYWGAGJ , OQGSI h Jbjje GdYQhV , GMGdI GdYWGAGJ h eSDhdjGJ GdehQO GJLGg GdeDSSI , GdJYGed eY GdYjfGJ h WQb GdOaY GdeJHYI dOi GOGQI GdeTJQjGJ , GdGYJeGOGJ GdeSJfOjI h OhQgG aj GdTQGA GdOhdj , JYQja GdGYJeGO GdeSJfOj h GOGQI GdJdNjU h GdJNRjf GdLeQcj ddehGO eYdbI GdQShe h JLGQIGdJQGfRjJ h GdJLGQI GdOhdjI , GdJYHjQGJ GdTGFYI aj GdQCS h aj GdhLg h GdLSO , egGQGJ GdJaGhV dOi ehXaj GOGQI GdeTJQjGJ , JUfjaGJ GdGSJQGJjLjGJ GdJaGhVjI habG ddJhbjJ h GdWQjbI h GdecGf , JUfjaGJ GSJQGJjLjGJ GdJaGhV habG dSdhc GdeaGhVjf , GOGQI GdJaGhV h GdTQhW GdYGeI ddONhd aj GdYWGAGJ h GdJYGbO eY GdeJYgOjf h GHQGe GdYbO GdGdcJQhfj(B.s
Keywords: (3GdGOGQIs; (3GdJLGQI GdNGQLjIs; (3GdJLGQI GdNGQLjI `` GOGQIs; (3GdTQGA `` GOGQIs